Electrolyte for lithium-sulfur secondary battery and lithium-sulfur secondary battery comprising same

By using specific electrolytes in lithium-sulfur secondary batteries, the differences in solubility of lithium polysulfide are optimized, and the problems of high resistance, low output characteristics and poor service life characteristics of lithium-sulfur secondary batteries are solved, thereby achieving lower resistance and improved output and life characteristics.

CN119768949APending Publication Date: 2025-04-04LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380064090.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-26
Filing Date
2023-10-12
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Due to the unsmooth conversion of lithium polysulfide, lithium-sulfur secondary batteries have high resistance, low output characteristics, and poor service life characteristics, making them difficult to apply.

Method used

Using an electrolyte containing lithium salt, non-aqueous solvent and additives, the mixed energy of the electrolyte and lithium polysulfide is calculated through COSMO-RS theory to ensure that Gmix1-Gmix2 and Gmix1-Gmix3 meet specific relationships to optimize the solubility difference of lithium polysulfide.

Benefits of technology

By optimizing the electrolyte, lithium-sulfur secondary batteries can successfully perform continuous reduction and conversion of lithium polysulfide during the discharge process, reducing resistance, improving output characteristics, reducing side reactions, and extending their life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768949A_ABST
    Figure CN119768949A_ABST
Patent Text Reader

Abstract

The present invention relates to an electrolyte for a lithium-sulfur secondary battery and a lithium-sulfur secondary battery comprising the same, the electrolyte for a lithium-sulfur secondary battery being capable of reducing the resistance of a lithium-sulfur secondary battery and improving output characteristics. The electrolyte for a lithium-sulfur secondary battery includes a lithium salt, a non-aqueous solvent, and an additive, in which a first mixing energy (Gmix1) of the electrolyte and dilithium pertetrasulfide (Li2S4), a second mixing energy (Gmix2) of the electrolyte and dilithium perhexapulfide (Li2S6), and a third mixing energy (Gmix3) of the electrolyte and dilithium peroctasulfide satisfy a predetermined relationship.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority to Korean Patent Application No. 10-2022-0139326 filed in the Korean Intellectual Property Office on October 26, 2022, the disclosure of which is incorporated herein by reference in its entirety.

[0003] The present invention relates to an electrolyte for a lithium-sulfur secondary battery capable of reducing the resistance of a lithium-sulfur secondary battery and improving output characteristics, and a lithium-sulfur secondary battery including the electrolyte. Background Art

[0004] As the use of secondary batteries expands to electric vehicles (EVs), energy storage systems (ESSs), etc., lithium-ion secondary batteries with relatively low energy storage density relative to weight are gradually reaching their limits. In recent years, interest in various next-generation secondary batteries with high energy density has been increasing, among which research and development of lithium-sulfur secondary batteries with theoretically high energy storage density relative to weight has also become increasingly active.

[0005] Generally, such a lithium-sulfur secondary battery refers to a chargeable / dischargeable battery system containing a sulfur molecule (e.g., S8) having an SS bond (sulfur-sulfur bond) or a sulfur-containing composite material as a positive electrode active material and containing metallic lithium as a negative electrode active material. Such a lithium-sulfur secondary battery has abundant reserves all over the world and can be manufactured at a relatively low cost by using sulfur, which has a small weight relative to metal, as a positive electrode active material, which makes it possible to realize a secondary battery with a very high energy density relative to weight.

[0006] like Figure 1 As shown in, during the discharge process of the lithium-sulfur secondary battery, a continuous reduction reaction of sulfur (such as S8) contained in the positive electrode and a continuous oxidation reaction of the metallic lithium contained in the negative electrode occur in each electrode and the electrolyte. When this continuous oxidation / reduction reaction occurs, various types of lithium polysulfides (LiPS) are formed in the electrolyte and are able to move between the electrodes. The solid lithium sulfide (Li2S) finally formed can be deposited on the negative electrode. For example, the reaction process of lithium polysulfide and lithium sulfide generated by the continuous reduction reaction of sulfur can be summarized as S8→Li2S8→Li2S6→Li2S4→Li2S2→Li2S, where S8, Li2S2 and Li2S can have a solid state, and the remaining lithium polysulfide (Li2S n ; n is 4, 6 or 8) can have a liquid state dissolved in an electrolyte.

[0007] However, in the process of sequential and continuous conversion of sulfur, the phases of lithium polysulfide and lithium sulfide are different from each other, and this conversion process is not smooth and does not proceed quickly, so that the lithium-sulfur secondary battery has a relatively high resistance and low output characteristics relative to the existing lithium-ion secondary battery. In addition, in the process of forming lithium polysulfide by continuous oxidation / reduction reaction, some lithium polysulfide dissolved in the electrolyte may have side reactions with the negative electrode, etc., which may be a factor that reduces the life characteristics of the lithium-sulfur secondary battery.

[0008] Such high resistance, low output characteristics, and life characteristics are major factors that make it difficult to apply lithium-sulfur secondary batteries, and as a result, there is a growing demand for the development of lithium-sulfur secondary batteries having lower resistance and improved output characteristics. Summary of the invention

[0009] Technical issues

[0010] The object of the present invention is to provide an electrolyte for a lithium-sulfur secondary battery, which can promote the continuous conversion process of lithium polysulfide, thereby reducing the resistance of the lithium-sulfur secondary battery and improving the output characteristics.

[0011] Another object of the present invention is to provide a lithium-sulfur secondary battery including the above electrolyte, thereby having improved output characteristics and life characteristics.

[0012] Technical Solution

[0013] According to one aspect of the present invention, there is provided an electrolyte for a lithium-sulfur secondary battery, the electrolyte for a lithium-sulfur secondary battery comprising a lithium salt, a nonaqueous solvent and an additive.

[0014] Among them, according to the COSMO-RS (real solvent-like conductor shielding model) theory calculated at room temperature (20±5°C), the first mixing energy (Gmix1) of the electrolyte and dilithium pertetrasulfide (Li2S4), the second mixing energy (Gmix2) of the electrolyte and dilithium perhexasulfide (Li2S6) and the third mixing energy (Gmix3) of the electrolyte and dilithium peroctasulfide satisfy the following relationship: Gmix1-Gmix2 is above 0.73 kcal / mol, and Gmix1-Gmix3 is above 0.80 kcal / mol.

[0015] According to another aspect of the present invention, there is provided a lithium-sulfur secondary battery, the lithium-sulfur secondary battery comprising:

[0016] A positive electrode containing sulfur as a positive electrode active material;

[0017] a negative electrode comprising metallic lithium;

[0018] a separator disposed between the positive electrode and the negative electrode; and

[0019] Electrolytes.

[0020] Beneficial Effects

[0021] The electrolyte of the present invention optimizes the solubility difference between lithium polysulfides generated during the charge / discharge process of a lithium-sulfur secondary battery.

[0022] It was confirmed that, by applying this electrolyte, the lithium-sulfur secondary battery can smoothly and quickly carry out continuous reduction and conversion of lithium polysulfide during its discharge process. The results confirmed that the lithium-sulfur secondary battery has lower resistance than previously known batteries of the same type and can also show improved output characteristics.

[0023] In addition, lithium-sulfur secondary batteries can smoothly carry out the conversion process of lithium polysulfide, etc., thereby reducing the side reactions between lithium polysulfide and the negative electrode, etc., which can also help improve the life characteristics of lithium-sulfur secondary batteries.

[0024] Therefore, the present invention can contribute to improving output characteristics and life characteristics which are the greatest obstacles to commercialization of lithium-sulfur secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a schematic diagram showing the formation of various types of lithium polysulfides in an electrolyte through oxidation and reduction reactions during the charge / discharge process of a lithium-sulfur secondary battery;

[0026] Figure 2a is a graph showing the relationship between Gmix1-Gmix2 (kcal / mol) of the electrolyte and the resistivity (mΩ) of the secondary battery at a state of charge (SOC) of 80% for lithium-sulfur secondary batteries manufactured using the electrolytes of Examples 1 to 3 and Comparative Examples 1 to 3;

[0027] Figure 2b is a graph showing the relationship between Gmix1-Gmix3 (kcal / mol) of the electrolyte and the resistivity (mΩ) of the secondary battery at a state of charge (SOC) of 80% for lithium-sulfur secondary batteries manufactured using the electrolytes of Examples 1 to 3 and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0028] Now, an electrolyte and a lithium-sulfur secondary battery including the same according to specific embodiments of the present invention will be described in detail with reference to the accompanying drawings.

[0029] Figure 1 is a schematic diagram showing the formation of various types of lithium polysulfides in an electrolyte through oxidation and reduction reactions during the charge / discharge process of a lithium-sulfur secondary battery.

[0030] According to one embodiment of the present invention, there is provided an electrolyte for a lithium-sulfur secondary battery, the electrolyte for a lithium-sulfur secondary battery comprising a lithium salt, a nonaqueous solvent and an additive.

[0031] Among them, according to the COSMO-RS (real solvent-like conductor shielding model) theory calculated at room temperature (20±5°C), the first mixing energy (Gmix1) of the electrolyte and dilithium pertetrasulfide (Li2S4), the second mixing energy (Gmix2) of the electrolyte and dilithium perhexasulfide (Li2S6), and the third mixing energy (Gmix3) of the electrolyte and dilithium peroctasulfide satisfy the following relationship: Gmix1-Gmix2 is above 0.73 kcal / mol, and Gmix1-Gmix3 is above 0.80 kcal / mol.

[0032] The present inventors have continuously studied the characteristics of lithium-sulfur secondary batteries to develop electrolytes capable of reducing resistance and improving output characteristics. In particular, the present inventors have conducted research from various angles to clarify which characteristics of the conversion process have a significant impact on the resistance and output of lithium-sulfur secondary batteries, because a continuous reduction / conversion process of S8 (solid) → Li2S8 (liquid) → Li2S6 (liquid) → Li2S4 (liquid) → Li2S2 (solid) → Li2S (solid) occurs during the discharge process of the lithium-sulfur secondary battery, and a phase change occurs during this process.

[0033] As a result of this ongoing research, the inventors have determined that for various types of lithium polysulfides (Li2S n ; n is 4, 6 or 8), the characteristics of the electrolyte have the greatest impact on reducing the resistance of the lithium-sulfur secondary battery.

[0034] In addition, as a result of further experiments by the inventors, it has been found that, among various types of lithium polysulfides, the composition of the electrolyte is controlled so that the difference between the first mixing energy (Gmix1) defining the compatibility and solubility of the electrolyte for dilithium pertetrasulfide (Li2S4) and the second and third mixing energies (Gmix2 and Gmix3) defining the solubility of the electrolyte for dilithium perhexasulfide (Li2S6) and dilithium peroctasulfide (Li2S8), etc., becomes larger than a predetermined level, thereby reducing the resistance of the lithium-sulfur secondary battery and improving the output characteristics, thereby completing the present invention.

[0035] It is speculated that this is because, as the solubility difference between various types of lithium polysulfides increases, the reduction and conversion process between liquid lithium polysulfides, which mainly occurs in the electrolyte, can proceed more smoothly. In addition, as the first mixing energy (Gmix1) of the electrolyte for dilithium pertetrasulfide (Li2S4) becomes relatively high (that is, the solubility of the electrolyte for Li2S4 becomes relatively low), the subsequent phase change process to the solid can also proceed smoothly.

[0036] Thus, when the electrolyte for lithium-sulfur secondary battery that satisfies the characteristics of one embodiment is used, the resistance of the secondary battery can be reduced during the charge / discharge process, and as a result, the output characteristics of the secondary battery can be improved. In addition, since the conversion process between lithium polysulfides proceeds more smoothly, the side reaction between lithium polysulfides and the negative electrode can also be suppressed, thereby further improving the life characteristics of the lithium-sulfur secondary battery.

[0037] In the electrolyte of the above embodiment, the first to third mixing energies refer to the mixing energies of the electrolyte and lithium polysulfide (Li2S n ; n is 4, 6 or 8) when mixed, and can be calculated according to quantum mechanical calculations by COSMO-RS theory based on the structural information of each molecule (see, for example, "COSMO-RS: From Quantum Chemistry to Fluid Phase Thermodynamics and Drug Design", A. Klamt, Elsevier; Amsterdam, the Netherlands, 2005, and Korean Unexamined Patent Publication No. 2019-0011963). In a more specific embodiment, the first to third mixing energies can be calculated using the commercially available COSMOtherm software (COSMOlogic GmbH & Co.KG) that performs quantum mechanical calculations by COSMO-RS theory.

[0038] The first to third mixing energies can reflect the electrolyte of one embodiment and each lithium polysulfide (Li2S n ; n is 4, 6 or 8). Because the electrolyte of one embodiment satisfies the specific composition and the like described below, the first mixing energy when mixed with Li2S4 is higher (i.e., the solubility is lower), and Li2S6 and Li2S8 can exhibit the characteristics of low second and third mixing energies (i.e., high solubility).

[0039] Thus, the electrolyte of one embodiment can satisfy the following relationship: Gmix1-Gmix2 is 0.73 kcal / mol or more, or 0.74 to 1.40 kcal / mol, or 0.80 to 1.10 kcal / mol, and Gmix1-Gmix3 is 0.80 kcal / mol or more, or 0.80 to 1.50 kcal / mol, or 0.85 to 1.20 kcal / mol, and the solubility difference between lithium polysulfides may appear large.

[0040] In addition, in a more specific embodiment, the electrolyte of one embodiment has Gmix2-Gmix3 of 0.05 kcal / mol or more, or 0.05 to 0.2 kcal / mol, or 0.06 to 0.1 kcal / mol, so that the electrolyte can also show some differences in the solubility of each of Li2S6 and Li2S8.

[0041] When the difference between the first to third mixing energies becomes larger than a certain level in this way, and each lithium polysulfide (Li2S n ; n is 4, 6 or 8) becomes greater than a certain level, the reduction and conversion process between the lithium polysulfides proceeds more smoothly, thereby further reducing the resistance of the lithium sulfur secondary battery and further improving the output. However, if the difference between the first to third mixing energies is too large, but the solubility of the electrolyte for any type of lithium polysulfide such as Li2S4 is too low, the output characteristics of the secondary battery may deteriorate.

[0042] On the other hand, in order to achieve the difference between the first to third mixing energies and ensure that each lithium polysulfide (Li2S n ; n is 4, 6 or 8), the first mixing energy (Gmix1) can be -3.02 kcal / mol to -0.02 kcal / mol, the second mixing energy (Gmix2) can be -3.39 kcal / mol to -0.83 kcal / mol, and the third mixing energy (Gmix3) can be -3.15 kcal / mol to -0.96 kcal / mol.

[0043] If the first mixing energy becomes too high, or the second and third mixing energies become too low, the conversion process between lithium polysulfides may not proceed smoothly, or the solubility of some lithium polysulfides may become low, which may deteriorate the output characteristics of the lithium-sulfur secondary battery. On the contrary, if the first mixing energy is too low, or the second and third mixing energies are too high, it becomes difficult to achieve the difference between the first to third mixing energies mentioned above, so that the resistance of the secondary battery may increase.

[0044] On the other hand, the electrolyte of one embodiment basically comprises a lithium salt, a non-aqueous solvent and additives, and particularly comprises a specific solvent composition as a non-aqueous solvent, and the concentration / content of the lithium salt and other additives is controlled within a specific range so as to satisfy the first to third mixing energies and their differences with each lithium polysulfide.

[0045] In order to make the electrolyte meet the above mixing energy range and difference, the non-aqueous solvent contains lithium polysulfide (Li2S n ; n is 4, 6 or 8) and a first organic solvent and a second organic solvent with different solubility, wherein the first organic solvent is used as a solvent with good solubility for lithium polysulfide, and the second organic solvent can be a non-solvent for lithium polysulfide. In particular, by adjusting the composition of the first organic solvent and the second organic solvent included as a non-solvent, the mixing energy range and the difference therebetween can be achieved.

[0046] In a specific embodiment, the non-aqueous solvent contains: 70 to 85 volume % or 70 to 80 volume % of an ether solvent as a first organic solvent, the ether solvent comprising a dialkyl ether solvent and an alkylene glycol dialkyl ether solvent; and 15 to 30 volume % or 20 to 30 volume % of a furan solvent and / or a tetrahydrofuran solvent as a second organic solvent of the non-solvent, wherein, based on the total volume of the non-aqueous solvent, the content of the dialkyl ether solvent can be 40 to 85 volume % or 40 to 80 volume %.

[0047] At this time, the second organic solvent of the furan or tetrahydrofuran solvent, and the first organic solvent of the dialkyl ether solvent and the alkylene glycol dialkyl ether solvent can be used as a non-solvent and a solvent having different solubility for lithium polysulfide, respectively. Therefore, when such non-solvent and solvent are contained within the above-mentioned optimal composition and content range, the difference between the above-mentioned first to third mixing energies is satisfied, so that the resistance of the lithium-sulfur secondary battery is further reduced and the output characteristics can be further improved.

[0048] In addition, the furan or tetrahydrofuran second organic solvent forms an SEI layer (solid electrolyte interface) on the surface of the metal lithium, thereby inhibiting the formation of lithium dendrites, and can inhibit the decomposition of the electrolyte on the surface of the negative electrode metal lithium, thereby improving the life characteristics of the secondary battery. Therefore, since the content of the second organic solvent is optimized, the life characteristics of the lithium-sulfur secondary battery can also be improved.

[0049] In contrast, when the content of the furan or tetrahydrofuran second organic solvent is too large, the solubility of the electrolyte for some lithium polysulfide may be excessively reduced, thereby possibly deteriorating the characteristics of the lithium-sulfur secondary battery. In addition, when the content of the furan or tetrahydrofuran second organic solvent becomes too small, or the content range of the dialkyl ether solvent in the first organic solvent becomes too small, etc., it is difficult to satisfy the difference between the first to third mixing energies described above, so that the resistance of the lithium-sulfur secondary battery may increase and its output characteristics may deteriorate.

[0050] In a more specific embodiment, the second organic solvent may include both a furan-based solvent and a tetrahydrofuran-based solvent, wherein the mixed volume ratio of the furan-based solvent to the tetrahydrofuran-based solvent may be 30:1 to 1:30, or 20:1 to 1:20.

[0051] In the above-mentioned non-aqueous solvent composition, the furan or tetrahydrofuran solvent can be a furan compound or tetrahydrofuran compound in which an alkyl group having 1 to 4 carbon atoms is substituted or unsubstituted, and specific examples thereof include at least one selected from the following: furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, 2-methyltetrahydrofuran and 4-methyltetrahydrofuran.

[0052] Among them, considering the difference between the above-mentioned first to third mixing energies, etc., 2-methylfuran, 2-methyltetrahydrofuran or 4-methyltetrahydrofuran or a combination of two or more selected therefrom can be preferably used. For example, 2-methylfuran can be used alone, or can be used in combination with 2-methyltetrahydrofuran or 4-methyltetrahydrofuran. For this combination, 2-methylfuran: 2-methyltetrahydrofuran or 4-methyltetrahydrofuran can be mixed in a volume ratio of 30:1 to 1:30 or 20:1 to 1:20.

[0053] In addition, as the dialkyl ether solvent, an ether compound to which an alkyl group having 1 to 10 carbon atoms or 1 to 5 carbon atoms is bonded can be used, and specific examples thereof include at least one selected from the following: dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane and methoxyethoxyethane.

[0054] In addition, as the alkylene glycol dialkyl ether solvent, a compound in which two or more alkylene glycol groups having 1 to 5 carbon atoms or 2 to 3 carbon atoms are bonded to an alkyl group having 1 to 5 carbon atoms via an ether bond (-O-) can be used. Specific examples thereof include at least one selected from the following: diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether.

[0055] Among them, taking into account the difference between the above-mentioned first to third mixing energies and the like, dimethoxyethane as a dialkyl ether solvent and diethylene glycol dimethyl ether as an alkylene glycol dialkyl ether solvent may be appropriately combined.

[0056] On the other hand, lithium salt is an electrolyte salt for increasing ion conductivity, and can be used without limitation as long as it is commonly used in the art. Specific examples of such lithium salt include at least one selected from the following: LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi (LiFSI) and (CF3SO2)3CLi. However, considering the conductivity of the lithium-sulfur secondary battery or the difference in meeting the above-mentioned mixing energy, a lithium salt in the form of a sulfonate, such as CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi or (CF3SO2)3CLi, can be appropriately used.

[0057] The lithium salt may be contained in the electrolyte at a concentration of 0.2 to 0.8 mol%, or 0.25 to 0.75 mol%, or 0.30 to 0.70 mol%, so that the above electrolyte can appropriately satisfy the difference between the first to third mixing energies, etc. If the concentration of the lithium salt is too low, the conductivity of the lithium-sulfur secondary battery may be insufficient, and if the concentration of the lithium salt is too high, it may be difficult to satisfy the difference between the first to third mixing energies, which may increase the resistance of the lithium-sulfur secondary battery.

[0058] On the other hand, in addition to the non-aqueous solvent and the lithium salt, the electrolyte of the above embodiment further comprises an additive for improving the characteristics of the lithium-sulfur secondary battery. Examples of such additives include at least one selected from the following: lithium nitrate (LiNO3), lithium thiocyanate (LiSCN), potassium nitrate (KNO3), cesium nitrate (CsNO3), magnesium nitrate (Mg(NO3)2), barium nitrate (Ba(NO3)2), lithium nitrite (LiNO2), potassium nitrite (KNO2) and cesium nitrite (CsNO2), among which lithium nitrate and / or lithium thiocyanate can be preferably used.

[0059] In addition, the content of the additive may be 0.8 to 4.0 wt %, 0.9 to 3.5 wt %, based on the total weight of the electrolyte. If the content of the additive is too low, the characteristics of the lithium-sulfur secondary battery may be insufficient, and if the content of the additive is too high, it is difficult to satisfy the difference between the first to third mixing energies, which may increase the resistance of the lithium-sulfur secondary battery.

[0060] As described above, the electrolyte of one embodiment contains a lithium salt and an additive and a non-aqueous solvent of a specific composition in a specific content range, thereby satisfying the difference between the first to third mixing energies described above, and exhibiting optimized solubility for lithium polysulfide formed during discharge of a sulfur secondary battery. As a result, the conversion process between lithium polysulfides can be promoted during charge / discharge of a lithium-sulfur secondary battery, the resistance of the secondary battery can be reduced, and the output characteristics and life characteristics thereof can be further improved.

[0061] In particular, when the distributions of the initial charging voltage and the charge termination voltage in response to the change in the charging current are respectively measured and derived for a lithium-sulfur secondary battery, and the resistivity in response to the state of charge (SOC) of the secondary battery is calculated therefrom, the secondary battery exhibits a low resistivity of less than 400 mΩ, or less than 50 to 400 mΩ, or 100 to 350 mΩ at an SOC of 80%.

[0062] On the other hand, the method of measuring and calculating such resistivity is specifically described in International Patent Publication WO2016 / 126075 and the like of the present inventor.

[0063] Therefore, according to another embodiment of the present invention, a lithium-sulfur secondary battery is provided, wherein the lithium-sulfur secondary battery comprises:

[0064] A positive electrode containing sulfur as a positive electrode active material;

[0065] a negative electrode comprising metallic lithium;

[0066] a separator disposed between the positive electrode and the negative electrode; and

[0067] An electrolyte according to an embodiment.

[0068] Such a lithium-sulfur secondary battery includes the electrolyte of one embodiment, and thereby can exhibit improved output characteristics and life characteristics as well as low resistance.

[0069] In the secondary battery of another embodiment, the positive electrode may include a positive electrode active material and a binder, and may further include a conductive material. In addition, the positive electrode may be a positive electrode in which an active material layer including a positive electrode active material, a binder, etc. is formed on a positive electrode collector.

[0070] At this time, the positive electrode current collector supports the active material layer and is not particularly limited as long as it has high conductivity and does not cause chemical changes in the corresponding battery. For example, copper, stainless steel, aluminum, nickel, titanium, heat-treated carbon; or copper or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc.; aluminum-cadmium alloy, etc. can be used.

[0071] In addition, the positive electrode current collector may have fine concavoconvexities formed on its surface to enhance the bonding strength with the active material layer, and may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, nonwoven fabrics, and the like.

[0072] The positive electrode active material may contain sulfur. More specifically, as the positive electrode active material, elemental sulfur (S8), organic sulfur compounds, sulfur-carbon composite materials, polymers ((C2S x ) n ; x=2.5 to 50, n≥2), etc. Considering the characteristics of the electrolyte of one embodiment, elemental sulfur (S8) may be appropriately used.

[0073] Based on 100 parts by weight of the total weight of the positive electrode, the content of the positive electrode active material containing sulfur may be 40 parts by weight to 80 parts by weight, preferably 50 parts by weight to 70 parts by weight. If the content of the positive electrode active material is reduced, the energy density of the secondary battery may be reduced, and if its content is too large, the conductivity and stability of the electrode may be reduced.

[0074] Furthermore, in addition to the above-mentioned positive electrode active material, the positive electrode may further include at least one additive selected from the group consisting of transition metal elements, Group IIIA elements, Group IVA elements, sulfur compounds of these elements, and alloys of these elements with sulfur.

[0075] Transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, Hg, etc., Group IIIA elements may include Al, Ga, In, Tl, etc., and Group IVA elements may include Ge, Sn, Pb, etc.

[0076] On the other hand, the binder is a component that assists the combination of the active material and the current collector. For example, the binder can be at least one selected from the following: polyvinylidene fluoride (PVdF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVdF / HFP), polyvinyl acetate, polyvinyl alcohol, polyvinyl ether, polyethylene, polyethylene oxide, alkylated polyethylene oxide, polypropylene, polymethyl (meth) acrylate, polyethyl (meth) acrylate, polytetrafluoroethylene (PTFE), polyvinyl chloride, polyacrylonitrile, polyvinyl pyridine, polyvinyl pyrrolidone, styrene-butadiene rubber, nitrile rubber, ethylene propylene diene monomer (EPDM) rubber, sulfonated EPDM rubber, fluororubber, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose and mixtures thereof, but are not necessarily limited thereto.

[0077] The amount of the binder added may generally be 1 to 15 parts by weight based on 100 parts by weight of the total weight of the positive electrode. If the content of the binder is less than 1 part by weight, the adhesion between the active material layer and the current collector may be insufficient, and if the content of the binder exceeds 15 parts by weight, the adhesion is improved, but the content of the positive electrode active material is correspondingly reduced, and the battery capacity may be reduced.

[0078] On the other hand, the conductive material is a component for improving conductivity, and there is no particular limitation as long as it is an electronic conductive material that does not cause chemical changes in the secondary battery. For example, as a conductive material, carbon black, graphite, carbon fiber, carbon nanotubes, metal powder, conductive metal oxide, organic conductive material, etc. can be used, and currently commercially available products may include acetylene black series (Chevron Chemical Company, Gulf Oil Company, etc.), Ketjen Black EC series (Armak Company's product), Vulcan XC-72 (Cabot Company's product) and Super P (MMM Company's product), etc. For example, acetylene black, carbon black, graphite, etc. can be used.

[0079] In addition, in the lithium-sulfur secondary battery of other embodiments, a filler may be optionally added to the positive electrode as a component for suppressing the expansion of the positive electrode active material containing sulfur. There is no particular limitation on such a filler as long as it can suppress the expansion of the electrode without inducing chemical changes in the battery. For example, it is possible to use: olefin polymers such as polyethylene and polypropylene; fibrous materials such as glass fiber and carbon fiber; etc.

[0080] The positive electrode can be prepared by dispersing the positive electrode active material, the conductive material and the binder in a dispersion medium (solvent) and mixing to form a slurry, coating the slurry on the positive electrode collector, and then drying and rolling it. As a dispersion medium, NMP (N-methyl-2-pyrrolidone), DMF (dimethylformamide), DMSO (dimethyl sulfoxide), ethanol, isopropanol, water and mixtures thereof can be used, but are not limited thereto.

[0081] In the secondary batteries of the other embodiments described above, the negative electrode may include metallic lithium, for example, it may include a lithium metal or alloy layer formed on a negative electrode current collector.

[0082] There is no particular limitation on this negative electrode current collector as long as it has high conductivity and does not cause chemical changes in the battery, and it can be selected from: copper, aluminum, stainless steel, zinc, titanium, silver, palladium, nickel, iron, chromium, alloys thereof, and combinations thereof. The surface of stainless steel may be treated with carbon, nickel, titanium, or silver, and an aluminum-cadmium alloy may be used as the alloy, in addition to which calcined carbon, a non-conductive polymer with a conductor treated surface, a conductive polymer, and the like may also be used. As the negative electrode current collector, a copper sheet is generally used.

[0083] The metallic lithium may be a lithium metal or an alloy. In this case, the lithium alloy contains an element capable of forming an alloy with lithium, specifically, it may be an alloy of lithium with one or more metals selected from the following: Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge and Al. The metallic lithium may be a sheet or foil, and in some cases, may have a form in which a lithium metal or a lithium alloy is deposited or coated on a current collector using a dry process, or may have a form in which a granular metal and alloy is deposited or coated using a wet process.

[0084] A conventional separator can be inserted between the positive electrode and the negative electrode. The separator is a physical separator having the function of physically separating the electrodes, and as long as it is used as a normal separator, it can be used without any special restrictions, and it is particularly preferred that it has low resistance to the movement of ions in the electrolyte and excellent wettability to the electrolyte. In addition, the separator separates or insulates the positive electrode and the negative electrode from each other and allows lithium ions to be transmitted between the positive electrode and the negative electrode. This separator is porous and can be made of non-conductive or insulating materials. The separator can be an independent component such as a film, or can be a coating added to the positive electrode and / or the negative electrode.

[0085] As an example of a polyolefin porous film that can be used as a separator, a film formed of a polymer can be used, and the polymer is a polyolefin polymer such as high-density polyethylene, linear low-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene, polypropylene, polybutene, polypentene, or a polymer mixed with these substances. As an example of a non-woven fabric that can be used as a separator, a non-woven fabric formed of a polymer can be used, and the polymer is a single use of polyphenylene ether, polyimide, polyamide, polycarbonate, polyethylene terephthalate, polyethylene naphthoate, polybutylene terephthalate, polyphenylene sulfide, polyacetal, polyether sulfone, polyether ether ketone, polyester, etc., or a polymer mixed with these substances, and, as a fiber form forming a porous cloth, this non-woven fabric includes a spunbond or melt-blown form formed by long fibers.

[0086] There is no particular restriction on the thickness of the separator, but it is preferably in the range of 1 μm to 100 μm, more preferably in the range of 5 μm to 50 μm. When the thickness of the separator is less than 1 μm, the mechanical properties may not be maintained, and when the thickness is greater than 100 μm, the separator acts as a resistance layer, thereby reducing battery performance. There is no particular restriction on the pore size and porosity of the separator, but the pore size is preferably 0.1 μm to 50 μm and the porosity is preferably 10% to 95%. When the pore size of the separator is less than 0.1 μm or the porosity is less than 10%, the separator acts as a resistance layer, and when the pore size is greater than 50 μm or the porosity is greater than 95%, the mechanical properties may not be maintained.

[0087] A lithium-sulfur secondary battery of another embodiment including the above-mentioned electrolyte, a positive electrode, a negative electrode, and a separator can be manufactured by a method in which the positive electrode faces the negative electrode, the separator is interposed therebetween, and then the electrolyte is injected.

[0088] On the other hand, lithium secondary batteries are not only suitable for battery cells used as power sources for small devices, but are also particularly suitable for use as unit cells of battery modules used as power sources for medium and large devices. In this regard, a battery module in which at least two lithium secondary batteries are electrically connected (in series or in parallel) can be provided.

[0089] Of course, various adjustments can be made to the number of lithium secondary batteries contained in the battery module, taking into account the purpose and capacity of the battery module. In addition, a battery pack of battery modules electrically connected according to conventional techniques in the art can also be provided. The battery module and the battery pack can be used as a power source for at least one medium or large device selected from the following: power tools; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV) and plug-in hybrid electric vehicles (PHEV); electric trucks; electric commercial vehicles; or power storage systems, but the present invention is not limited thereto.

[0090] Hereinafter, preferred examples are given to facilitate understanding of the present invention. However, it will be apparent to those skilled in the art that these examples are merely illustrations of the present invention, that various changes and variants can be made within the scope and spirit of the present invention, and that these changes and variants are intended to fall within the scope of the appended claims.

[0091] Examples 1 to 3 and Comparative Examples 1 to 3: Preparation of electrolyte for lithium-sulfur secondary battery

[0092] The nonaqueous solvent was mixed according to the composition shown in Table 1 below, and then the lithium salt and the additive were dissolved in the concentration and content shown in Table 1 to produce the electrolyte of each of Examples and Comparative Examples.

[0093] * DME: 1,2-dimethoxyethane; LiFSI: (SO2F)2NLi

[0094] Experimental Example 1: Calculation of the first to third mixing energies (Gmix1 to 3) when mixing electrolyte and lithium polysulfide

[0095] The commercial COSMOtherm software (COSMOlogic GmbH & Co.KG) based on COSMO-RS theory was used to calculate the reaction temperature of the electrolyte of the embodiment or comparative example with lithium polysulfide (Li2S n ; n is 4, 6 or 8) mixing energy when mixed, and the calculation results are summarized in the following Table 2:

[0096]

[0097] Referring to Table 2, it was confirmed that the electrolytes of Examples 1 to 3 contained a nonaqueous solvent of a specific composition, and contained a lithium salt and an additive at specific concentrations and contents, and satisfied the following characteristics: Gmix1-Gmix2 was 0.73 kcal / mol or more, and Gmix1-Gmix3 was 0.80 kcal / mol or more.

[0098] On the other hand, it was confirmed that the electrolytes of Comparative Examples 1 to 3 showed relatively low values ​​of Gmix1-Gmix2 and Gmix1-Gmix3 because the composition of the nonaqueous solvent was different from that of the Examples.

[0099] Test Example 2: Fabrication of lithium-sulfur secondary battery and evaluation of resistivity

[0100] Electrolytes

[0101] The electrolytes of Examples or Comparative Examples were used.

[0102] Cathode Manufacturing

[0103] 95 parts by weight of a sulfur-carbon composite material (S:C=70:30 weight ratio) as a positive electrode active material (based on the total weight of the positive electrode, the sulfur content alone was set to 67.5 weight %, and activated carbon with a pore volume of 1.8 cm3 / g was used as the carbon material) and 5 parts by weight of styrene-butadiene rubber / carboxymethyl cellulose (SBR:CMC=7:3) as a binder were mixed to prepare a positive electrode slurry composition, and the prepared slurry composition was coated on a current collector (Al foil), dried at 50°C for 12 hours, and pressed using a roller press to manufacture a positive electrode (at this time, the porosity of the electrode was set to 65%).

[0104] Lithium-sulfur battery manufacturing

[0105] The positive electrode manufactured as described above and the lithium metal negative electrode having a thickness of 150 μm were placed face to face with each other, a polyethylene (PE) separator was inserted between them, and then an electrolyte was injected to manufacture a coin cell type lithium sulfur secondary battery. On the other hand, in the manufacture of the battery, the positive electrode was used by punching out at Φ15, the polyethylene separator was used by punching out at Φ19, and the metal lithium was used by punching out at Φ16.

[0106] The resistivity of the lithium-sulfur secondary battery manufactured using the electrolyte of the example or the comparative example was measured and calculated according to the method described in International Patent Publication WO2016 / 126075.

[0107] More specifically, for a lithium-sulfur secondary battery, first, for each temperature and state of charge (SOC) of the secondary battery, a plurality of charging initial voltage data and a plurality of charging end voltage data are measured as the charging current changes, and stored in a memory. Next, a charging end IV distribution is determined from a plurality of charging end voltage data, and an intersection point is determined where the charging end IV distribution intersects with a boundary line corresponding to a charging upper limit current or a charging upper limit voltage pre-set as a charging upper limit condition. In addition, an initial charging IV distribution is determined from a plurality of initial charging voltage data, and a first differential value of the initial charging IV distribution calculated based on the current value at the intersection is determined. Then, the determined first-order differential value is determined and calculated as a resistivity corresponding to the temperature and the state of charge of the secondary battery.

[0108] At this time, a current greater than 2 ea was used, and the resistivity at the maximum current (Imax) was calculated according to the following formula 1.

[0109] [Formula 1]

[0110] R=△V / Imax=(OCV-Vfinal@Imax) / Imax

[0111] For the batteries manufactured using the electrolytes of the embodiments and comparative examples, the resistivity at SOC 80% is summarized in the following Table 3. Figure 2a The relationship between Gmix1-Gmix2 (kcal / mol) of the electrolyte and the resistivity (mΩ) of the secondary battery at a state of charge (SOC) of 80% is shown for lithium-sulfur secondary batteries manufactured using the electrolytes of Examples 1 to 3 and Comparative Examples 1 to 3, and Figure 2b The relationship between Gmix1-Gmix3 (kcal / mol) of the electrolyte and the resistivity (mΩ) of the secondary battery at a state of charge (SOC) of 80% for lithium-sulfur secondary batteries manufactured using the electrolytes of Examples 1 to 3 and Comparative Examples 1 to 3 is shown.

[0112]

[0113] Refer to Table 3 and Figure 2a and Figure 2b It was confirmed that the lithium-sulfur secondary battery manufactured using the electrolyte of the embodiment exhibited lower resistivity than the comparative example at SOC 80%. In particular, it was confirmed that the embodiment exhibited Gmix1-Gmix2 of 0.73 kcal / mol or more and Gmix1-Gmix3 of 0.80 kcal / mol or more, which were greater values ​​than the electrolyte of the comparative example, thereby showing reduced resistivity and excellent output.

Claims

1. An electrolyte for a lithium-sulfur secondary battery, the electrolyte for a lithium-sulfur secondary battery comprising a lithium salt, a nonaqueous solvent and an additive, in, According to the COSMO-RS (real solvent-like conductor shielding model) theory, the first mixing energy (Gmix1) of the electrolyte and dilithium pertetrasulfide (Li2S4), the second mixing energy (Gmix2) of the electrolyte and dilithium perhexasulfide (Li2S6), and the third mixing energy (Gmix3) of the electrolyte and dilithium peroctasulfide satisfy the following relationship at room temperature (20±5°C): Gmix1-Gmix2 is 0.73 kcal / mol or more, and Gmix1-Gmix3 are 0.80 kcal / mol or more.

2. The electrolyte for lithium-sulfur secondary batteries according to claim 1, wherein Gmix1-Gmix2 is 0.74 kcal / mol to 1.40 kcal / mol, and Gmix1-Gmix3 are 0.80 kcal / mol to 1.50 kcal / mol.

3. The electrolyte for lithium-sulfur secondary batteries according to claim 1, wherein Gmix2-Gmix3 is 0.05 kcal / mol or more.

4. The electrolyte for lithium-sulfur secondary batteries according to claim 1, wherein The first mixing energy (Gmix1) is -3.02 kcal / mol to -0.02 kcal / mol, The second mixing energy (Gmix2) is -3.39 kcal / mol to -0.83 kcal / mol, and The third mixing energy (Gmix3) is -3.15 kcal / mol to -0.96 kcal / mol.

5. The electrolyte for lithium-sulfur secondary batteries according to claim 1, wherein The non-aqueous solvent comprises lithium polysulfide (Li2S n ; n is 4, 6 or 8) having a first organic solvent and a second organic solvent with different solubilities, and The second organic solvent is a non-solvent for the lithium polysulfide.

6. The electrolyte for lithium-sulfur secondary batteries according to claim 5, wherein The non-aqueous solvent comprises: 70% to 85% by volume of an ether solvent as the first organic solvent, the ether solvent comprising a dialkyl ether solvent and an alkylene glycol dialkyl ether solvent; and 15% to 30% by volume of a furan solvent or a tetrahydrofuran solvent as the second organic solvent, Wherein, based on the total volume of the non-aqueous solvent, the content of the dialkyl ether solvent is 40 volume % to 85 volume %.

7. The electrolyte for lithium-sulfur secondary batteries according to claim 6, wherein The furan-based solvent or the tetrahydrofuran-based solvent comprises at least one selected from the group consisting of furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-propylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, 2-methyltetrahydrofuran and 4-methyltetrahydrofuran.

8. The electrolyte for lithium-sulfur secondary batteries according to claim 6, wherein The dialkyl ether solvent comprises at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane and methoxyethoxyethane.

9. The electrolyte for lithium-sulfur secondary batteries according to claim 6, wherein The alkylene glycol dialkyl ether solvent comprises at least one selected from the following: diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether and polyethylene glycol methyl ethyl ether.

10. The electrolyte for lithium-sulfur secondary batteries according to claim 1, wherein The lithium salt is dissolved in the non-aqueous solvent at a concentration of 0.2 mol % to 0.8 mol %.

11. The electrolyte for lithium-sulfur secondary batteries according to claim 1, wherein The lithium salt comprises at least one selected from the group consisting of LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi(LiFSI) and (CF3SO2)3CLi.

12. The electrolyte for lithium-sulfur secondary batteries according to claim 1, wherein The additive may be included in an amount of 0.8 wt % to 4.0 wt % based on the total weight of the electrolyte.

13. The electrolyte for lithium-sulfur secondary batteries according to claim 1, wherein The additive comprises at least one selected from the following: lithium nitrate (LiNO3), lithium thiocyanate (LiSCN), potassium nitrate (KNO3), cesium nitrate (CsNO3), magnesium nitrate (Mg(NO3)2), barium nitrate (Ba(NO3)2), lithium nitrite (LiNO2), potassium nitrite (KNO2) and cesium nitrite (CsNO2).

14. A lithium-sulfur secondary battery, comprising: A positive electrode containing sulfur as a positive electrode active material; a negative electrode comprising metallic lithium; A separator disposed between the positive electrode and the negative electrode; and The electrolyte according to claim 1.

15. The lithium-sulfur secondary battery according to claim 14, wherein: The positive electrode active material includes elemental sulfur (S8).

16. The lithium-sulfur secondary battery according to claim 14, wherein When distributions of an initial charge voltage and a charge termination voltage in response to a change in a charge current are respectively measured and derived for the lithium-sulfur secondary battery, and a resistivity in response to a state of charge (SOC) of the secondary battery is calculated therefrom, the secondary battery exhibits a resistivity of 400 mΩ or less at an SOC of 80%.

Citation Information

Patent Citations

  • Single-Input Single-Output (SISO) Physical Layer Key Exchange

    KR1020220139326A

  • Method for determining resistance factor of secondary battery, and apparatus and method for estimating charging power using resistance factor

    WO2016126075A1